Comparison of volumetric loss and surface roughness of composite dental restorations obtained by additive and subtractive manufacturing methods - Neslihan Güntekin; Ali Rıza Tunçdemir (Heliyon, 2024)
Statement of problem: Permanent crown materials produced with new generation additive manufacturing and traditional subtractive manufacturing materials have not been compared in terms of wear resistance. Purpose: This study aims to compare the volumetric loss related to wear and resulting surface roughness after aging in a chewing simulator between resin nano ceramics produced with milling technique and permanent crown materials produced with three dimensional (3D) printing. Materials and methods: Three different hybrid composite-ceramic (HCC) (The three materials are GC: Cerasmart, VE: Vita Enamic, and GV: Grandio Voco.) and one 3D printed definitive crown resin (FormLabs Permanent Crown Resin) were investigated before aging (n:8), the surface roughness of all samples was measured with a profilometer, and 1 randomly selected sample from each subgroup was imaged with scanning electron microscope (SEM). 3D scans of each sample were obtained with a desktop scanner. Thermomechanical aging was performed using a chewing simulator. Four hundred thousand cycles were completed under a vertical occlusal force of 49 ± 0.7 N with a thermal cycle of 1.7 Hz 5–55° and with a dwell time of 120 s, mimicking 2 years of aging. The imaging procedures were repeated, and the change in surface roughness was evaluated. 3D images were also overlapped, and the volumetric loss was calculated with the relevant inspector software. The data obtained were analyzed by two-way ANOVA (p < 0.05). Result: The results showed significant statistical differences for both parameters (p > 0.05). The highest volumetric loss was found in the GV group while the lowest volumetric loss was in the VE group. The highest surface roughness values were observed in the GV group, while the lowest values belonged to the VE one. Conclusion: Of the restorative materials evaluated, the VE group is suitable for long-term restorations, whereas the GV one is suitable for medium-term restorations. It is promising in terms of 3D printing technologies that the 3D material gives comparable results with the GV group. Clinical i̇mplication: Additive manufacturing techniques are a successful method that accelerates the manufacturing process. Permanent crown resins are promising alternatives to conventional production.